Mediation skills and strategies. A practical guide - Whatling, Tony (London, 2012)
"Mediation is a process that can be used to resolve conflict in many different dispute contexts. This book focuses on the essential skills and strategies needed by any mediator to be successful in their work. Tony Whatling draws on his extensive experience in the field of mediation to explain the range of skills and strategies that are commonly used, as well as why you would use different skills and when they are best employed. The author shows how, by adopting these techniques, a mediator can manage challenging conflicts. It features the use of questioning skills and how they can be used effectively, as well as how to deal with high emotion and negative responses. This book is essential for anyone who wants to improve their mediation skills, whether as a trainee, novice or experienced professional."